Soaking time of lime solutions (Citrus aurantifolias) against the metal content reduction of cadmium in green shellfish (Perna viridis) - Arie Dwi Alristina; Dewinta Hayudanti; Rizky Dzariyani Laili; Rossa Kurnia Ethasari (International Journal of Public Health Science (IJPHS), 2021)
Indonesia has the potential for large marine and fisheries resources, reaching 23.26 million tons per year. Green shellfish (Perna viridis) are a source of animal protein that can be classified as Complete Protein because of its high levels of essential amino acids. These green shellfish are cheaper than other seafood products. However, heavy metals can be absorbed by shellfish, which is cadmium (Cd) which if consumed can accumulate in the body, cause health problems and lead to death. Therefore, research is needed to reduce cadmium levels in green shellfish, including using a lime solution (Citrus aurantifolia). This study was to determine the effectiveness of the soaking time of lime in reducing the cadmium levels in green shellfish. The research was an experimental with a pretest-posttest group design. Kruskal Wallis and Mann Whitney test was used to analyze data by SPSS. The results showed a significant difference (p<0.05) that means the longer the soaking time, the longer the time for the citrate ions to react with metal cadmium, more cadmium is bound to the lime solution. It showed that soaking green shellfish with lime solution for 120 minutes was the most effective to reduce 73.77% of cadmium levels in green shellfish.